LIVING HADIST DAN KETAHANAN SOSIAL PANGAN: PROGRAM JUMAT BERBAGI DI MASJID RAUDHATUL JANNAH - Ahmad Baiquni (CV. Denasya Smart Publisher, 2026)
Amid the growing complexity of social problems, particularly inequality in food access, Islamic teachings offer solutions that are not merely normative but also practical through socio-religious practices. The hadith of the Prophet Muhammad (peace be upon him), as a source of Islamic teachings, is not only understood textually but also lived through social actions within Muslim communities, as examined in the Living Hadith approach. This study aims to analyze almsgiving practices in the Friday Sharing Program at Raudhatul Jannah Mosque as an actualization of Living Hadith in supporting social food resilience. This research employs a descriptive qualitative approach, with data collected through observation, semi-structured interviews with mosque administrators and beneficiaries, and literature review. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the Friday Sharing Program functions not only as an individual act of worship but also as a community-based food distribution mechanism that contributes to meeting the food needs of vulnerable groups. This practice reflects the transformation of hadith teachings on almsgiving from normative texts into contextual and responsive social actions. The study highlights the strategic role of mosques as agents of social food resilience through the optimization of prophetic-based almsgiving practices.